Pengelolaan Sarana Dan Prasarana Dalam Mendukung Kegiatan Pembelajaran Yang Optimal Di PAUD - Suhardi, Suhardi; Rahmadini, Putri Fauziah; Tussadiyah, Halimah; Wirdatunnabilah, Wirdatunnabilah (JURNAL MANAJEMEN PENDIDIKAN, 2025)
MANAGEMENT OF FACILITIES AND INFRASTRUCTURE IN SUPPORTING OPTIMAL LEARNING ACTIVITIES IN EARLY CHILDHOOD EDUCATIONManagement of facilities and infrastructure is one of the key elements to support the success of learning in Early Childhood Education (PAUD). Adequate facilities can create a safe, comfortable, and enjoyable learning atmosphere and provide the right stimulation for child development. This study applies a qualitative method with a literature study approach, aiming to describe how important it is to manage facilities and infrastructure effectively and efficiently. The findings of this study indicate that good management starting from planning, procurement, use, to maintenance contributes significantly to the quality of education and the success of early childhood learning.